AARP Research Data 2018
DOI: 10.26419/res.00246.005
|View full text |Cite
|
Sign up to set email alerts
|

Loneliness and Social Connections: A National Survey of Adults 45 and Older: Dataset

Abstract: 20% off Sunday through Thursday and 10% off Friday and Saturday, plus a $10-per-day physical damage waiver. Visit website for full offer details. 5% off leisure daily, weekly, weekend, and monthly base rates, plus a free upgrade on compact through full-size car class bookings. * * Subject to availability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 0 publications
0
23
0
Order By: Relevance
“…According to the National Institute on Aging, 1 in 4 adults aged 65 and older is socially isolated [11]. Aging adults are a high-risk group for social isolation and loneliness, a leading indicator of which is the size and diversity of a person's social network [12,13]. Compared to other populations, older adults have smaller social circles because of a variety of factors including deaths of family and friends, retirement, declining health, mobility challenges, social isolation, and perceptions of loneliness [14].…”
Section: The (In)visible Impacts Of Inequitable Participationmentioning
confidence: 99%
“…According to the National Institute on Aging, 1 in 4 adults aged 65 and older is socially isolated [11]. Aging adults are a high-risk group for social isolation and loneliness, a leading indicator of which is the size and diversity of a person's social network [12,13]. Compared to other populations, older adults have smaller social circles because of a variety of factors including deaths of family and friends, retirement, declining health, mobility challenges, social isolation, and perceptions of loneliness [14].…”
Section: The (In)visible Impacts Of Inequitable Participationmentioning
confidence: 99%
“…People who are lonely and socially isolated are more likely to have health problems, which can have serious financial implications. According to a 2018 study by the AARP Foundation, social isolation among midlife and older adults is associated with an estimated $6.7 billion in additional Medicare spending annually [6].…”
Section: Importance Of Social Connectivitymentioning
confidence: 99%
“…Of note, many of the hobbies the participants described were individual pursuits, which potentially protected them from experiencing rejection or more stigma. Although, research suggests that chronically lonely individuals to tend to turn to individual activities to cope, paradoxically maintaining the loneliness [8], even the "selfabsorbed" interests of participants offset depression. In fact, personal interests that a participant "lives for" connected him to a "we" in public (i.e.…”
Section: Living and Lonelinessmentioning
confidence: 99%
“…This pattern is not surprising as, since the advent of effective antiretroviral therapy, more adults with HIV now live into old age which is itself associated with a high prevalence of loneliness [4]. In fact, earlier research identified loneliness as a frequent source of emotional distress that negatively affects quality of life among people living with HIV [5,6], with 57% of HIV-positive adults over the age of 50 experiencing loneliness [7] compared to 35% of adults over the age of 45 in the United States [8]. Thus, understanding and addressing loneliness in those aging with HIV could improve quality of life, an important treatment target reflective of person-centred chronic care [9], overall health in general, and extend lifespan for persons living with HIV [7].…”
Section: Introductionmentioning
confidence: 99%